NEUTRON SCATTERING AND DIFFRACTION STUDIES OF FLUIDS AND FLUID-SOLID INTERACTIONS - Cole D.R.; Herwig K.W.; Mamontov E.; Larese J.Z. (My University, 2006)
There can be no disputing the fact that neutron diffraction and scattering have made a clear contribution to our current understanding of the structural and dynamical characteristics of liquid water and water containing dissolved ions at ambient conditions and to a somewhat lesser degree other state conditions involving a change in temperature and pressure. Indeed, a molecular-level understanding of how fluids (e.g., water, CO2, CH4, higher hydrocarbons, etc.) interact with and participate in reactions with other solid earth materials are central to the development of predictive models that aim to quantify a wide array of geochemical processes. The importance of the hydrogen-bond interaction, in water and other important hydrogenous fluids, has been highlighted as well as the sensitivity of the network to perturbations by a change in physical conditions or proximity to solute molecules and interfaces. Despite the large body of work that documents the nature of hydrogen bonding and associated interactions with its local surroundings, it is premature to assume that we have a complete understanding of the mechanisms that give rise to the particular properties exhibited by water and other simple molecular fluids. This is particularly true as one goes both above and below ambient conditions. For example, there is continuing discussion on the relation between the behavior of supercooled water, the structure of the amorphous ices, the behavior of molecular fluids at interfaces and the incorporation of simple molecules in hydrate clathrates. This is of particular interest since we have seen that nanoporous confinement of water at ambient conditions leads to structural and dynamical features that emulate the super-cooled state. In the context of natural systems, interrogation of fluids and fluid-solid interactions at elevated temperatures and pressures is an area requiring much more work, particularly for complex solutions containing geochemically relevant cations, anions, and other important dissolved species such CO2 or CH4. We have tried to describe a series of prototypical interfacial and surface problems using neutron scattering to stimulate the thinking of earth scientists interested applying some of these approaches to confined systems of mineralogical importance. Our ability to predict the molecular-level properties of fluids and fluid-solid interactions relies heavily on the synergism between experiments such as neutron diffraction or inelastic neutron scattering and molecular-based simulations. Tremendous progress has been made in closing the gap between experimental observations and predicted behavior based on simulations due to improvements in the experimental methodologies and instrumentation on the one hand, and the development of new potential models of water and other simple and complex fluids on the other. For example there has been an emergence of studies taking advantage of advanced computing power that can accommodate the demands of ab initio molecular dynamics. On the neutron instrumentation side while much of the quasielastic work described above has been performed using instrumentation located at reactor based sources, the advent of 2nd generation spallation neutron sources like ISIS, new generation sources like the SNS at the Oak Ridge National Laboratory and the low repetition rate 2nd target station at ISIS offer significant opportunities for the study of interfacial and entrained liquids. At the very least, an improvement of the counting statistics by one to two orders of magnitude on many instruments such as vibrational and time-of-flight spectrometers at SNS will allow parametric studies of many systems which otherwise would be prohibitively time consuming. The extended-Q SANS diffractometer at SNS will offer very high intensity and unparalleled Q-range to extend the accessible length scale in the real space, from 0.05 nm to 150 nm. The backscattering spectrometer will provide very high intensity and excellent energy resolution through unprecedented range of energy transfers, thereby allowing simultaneous studies of translational and rotational diffusion components in various systems. The vibrational spectrometer with two orders of magnitude improvement in performance and the capability to perform simultaneous structural measurements should present exciting opportunities to and engender an entire new population of users in the neutron community. Copyright © Mineralogical Society of America.